Multi-omics reveals the phyllosphere microbial community and material transformations in cigars - Wang, Xiaoyu; Yang, Shuai; Gao, Qiang; Dai, Youqing; Tian, Lei; Wen, Liang; Yan, Honghao; Yang, Long; Hou, Xin; Liu, Peng; Zhang, Li (Frontiers in Microbiology, 2024)
The quality of fermented plant leaves is closely related to the interleaf microorganisms and their metabolic activities. In this experiment, a multi-omics analysis was applied to investigate the link between the structural composition of the phyllosphere microbial community and the main metabolites during the fermentation process. It was found that the whole fermentation process of cigar leaves could be divided into three stages, in which the Mid-Stage was the most active period of microbial metabolic activities and occupied an important position. Staphylococcus, Brevundimonas, Acinetobacter, Brevibacterium, Pantoea, Aspergillus, Wallemia, Meyerozyma, Sampaiozyma, Adosporium and Trichomonascus played important roles in this fermentation. Staphylococcus and Aspergillus are the microorganisms that play an important role in the fermentation process. Staphylococcus were strongly correlated with lipids and amino acids, despite its low abundance, Stenotrophomonas is importantly associated with terpene and plays a significant role throughout the process. It is worth noting that Wapper exists more characteristic fungal genera than Filler and is more rapid in fermentation progress, which implies that the details of the fermentation process should be adjusted appropriately to ensure stable quality when faced with plant leaves of different genotypes. This experiment explored the relationship between metabolites and microorganisms, and provided a theoretical basis for further optimizing the fermentation process of plant leaves and developing techniques to improve product quality. Biomarker is mostly present in the pre-fermentation phase, but the mid-fermentation phase is the most important part of the process.